Maternal Smoking During Pregnancy Induces Persistent Epigenetic Changes Into Adolescence, Independent of Postnatal Smoke Exposure and Is Associated With Cardiometabolic Risk - Rauschert, Sebastian; Melton, Phillip E.; Burdge, Graham; Craig, Jeffrey M.; Godfrey, Keith M.; Holbrook, Joanna D.; Lillycrop, Karen; Mori, Trevor A.; Beilin, Lawrence J.; Oddy, Wendy H.; Pennell, Craig; Huang, Rae-Chi (Frontiers in Genetics, 2019)
Background Several studies have shown effects of current and maternal smoking during pregnancy on DNA-methylation of CpG sites in newborns and later in life. Here we hypothesized that there are long-term and persistent epigenetic effects following maternal smoking during pregnancy on adolescent offspring DNA methylation, independent of paternal and postnatal smoke exposure. Further, we explored the association between DNA methylation and cardiometabolic risk factors at 17 years of age. Materials and Methods DNA methylation was measured using the Illumina HumanMethylation450K BeadChip in whole blood from 995 participants attending the 17-year follow-up of the Western Australian Pregnancy Cohort (Raine) Study. Linear mixed effects models were used to identify differential methylated CpGs, adjusting for parental smoking during pregnancy, and paternal, passive and adolescent smoke exposure. Additional models examined the association between DNA methylation and paternal, adolescent and passive smoking over the life-course. Offspring DMCpGs identified were analysed against cardiometabolic risk factors (blood pressure, triacylglycerols (TG), high-density lipoproteins cholesterol (HDL-C) and body mass index). Results We identified 23 CpGs (genome wide p-level: 1.06 × 10-7), that were associated with maternal smoking during pregnancy, including associated genes AHRR (cancer development), FTO (obesity), CNTNAP2 (developmental processes), CYP1A1 (detoxification), MYO1G (cell signalling) and FRMD4A (nicotine dependence). A sensitivity analysis showed a dose dependent relationship between maternal smoking and offspring methylation. These results changed little following adjustment for paternal, passive or offspring smoking and there were no CpGs identified that associated with these variables. Two of the 23 identified CpGs (cg00253568 (FTO) and cg00213123 (CYP1A1)) were associated with either TG (males and females), diastolic blood pressure (females only) or HDL-C (males only), after Bonferroni correction. Discussion This study demonstrates a critical timing of cigarette smoke exposure over the life-course for establishing persistent changes in DNA methylation into adolescence in a dose dependent manner. There were significant associations between offspring CpG methylation and adolescent cardiovascular risk factors, namely TG, HDL-C and diastolic blood pressure. Future studies on current smoking habits and DNA methylation should consider the importance of maternal smoking during pregnancy and explore how the persistent DNA methylation effects of in utero smoke exposure increase cardiometabolic risk.